PERANCANGAN DESAIN USER INTERFACE/USER EXPERIENCE DENGAN MODEL USER CENTERED DESIGN PADA E-COMMERCE CAT ARJUNA - Permana, Dhimas Andy; Sagirani, Tri; Ayuningtyas, Ayuningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
Arjuna Paint Shop is a business engaged in the production and sale of paint and other supporting tools. Established since April 2011, Arjuna Paint products are well received by the public as personal needs, colorists and businesses such as shoescare. In running its business, the Arjuna Paint shop also utilizes technology in online marketing by providing information using the website. The problem that occurs on the Arjuna Cat shop website is that there are no complex and systematic transaction features. Users when registering as agents are still via telephone/email, improper website layout makes users uncomfortable, Cat Arjuna shop has decreased revenue because the website has never been evaluated and repaired regularly. Based on these problems, a user interface/user experience design was designed and produced a Cat Arjuna e-commerce prototype using a user centered design (UCD) model. In the evaluation process of prototype testing, an in-depth interview process was carried out with shop owners and also Cat Arjuna customers. Evaluation of the prototype was carried out by distributing a system usability scale (SUS) questionnaire to 30 respondents to evaluate the product and as a benchmark for user perceptions. From the results of testing the prototype, an average of 81 is included in the "excellent" category, which means that the design is accepted by the user.